Vogt-Koyanagi-Harada disease. Issue 6 (November 2021) - Joye, Ashlin; Suhler, Eric
Abstract : Purpose of review: Here, we provide an overview of Vogt-Koyanagi-Harada disease (VKH), including recent updates in our understanding of disease pathophysiology, classification and therapeutics. Recent findings: Advancements in bioinformatics, metabolomics and genomics investigations continue to illuminate VKH pathogenesis, and may provide insight into future therapeutic options. Multimodal imaging is indispensable in the initial evaluation of VKH, and is becoming increasingly important in understanding disease pathogenesis, as well as monitoring therapeutic response. Enhanced VKH classification criteria, released in 2021, provide standardized guidelines and terminology for clinical and research purposes. Summary: Modern research and imaging techniques continue to improve our understanding of VKH; more work is needed to further elucidate pathogenic mechanisms and establish optimal therapeutic recommendations.